Potret Budaya Melayu dalam Perencanaan Karier Siswa Di Sma Negeri 9 Kota Bengkulu - heni Sulusyawati (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2018)
This study aims to find out how portraits of Malay culture in student career planning at SMA Negeri 9 Bengkulu City. This research is a qualitative descriptive study. The approach used to better understand what phenomena experienced by research subjects in the natural setting context by utilizing natural setting methods. Data analysis techniques use the Spradley model, namely domain analysis, taxonomic analysis, componential analysis, and discovering cultural themes. Data analysis is done directly in the field together with data collection. Based on the results of data analysis, it can be concluded that: Students who have a Malay culture background already have a good career planning, this is indicated by the students can understand themselves, students can find out various information about the world of work, and students can match their potential with various information about the world of work .